LIGAND INDUCED CHEMOTAXIS OF MACROPHAGE CELL LINE U937 - A. B. Filina; O. A. Svitich; L. V. Gankovskaya; P. A. Labzhinov; T. M. Parfenova; V. V. Zverev (Медицинская иммунология, 2014)
Treatment of malignant tumors is among challenging issues of clinical medicine. Dissemination and matestasis of tumor cells plays a major role in oncology, being immediately dependent on chemotaxis of tumor cells. Hence, the aim of our study is to evaluate migration of tumor cells, in terms of ligand-mediated chemotaxis of a human U 937 lymphoma cell line. Synthetic TLR ligands (DNA_lig, RNA_lig) were used as chemoattractants. Assessment of time-dependent TLR expression by the migrating cells (including TLR2, TLR3, TLR7, TLR9) was carried out by means of real-time PCR, using Boyden’s chamber system for the migration assays. We have revealed an increased cell migration towards DNA_ lig and TNFα gradient. Expression of TLR2, TLR7 and TLR9 was found to be increased under the influence of TNFα (respectively 1.5-, 4- and 19-fold). Under the influence of DNA_lig, TLR9 expression was 105-fold increased, whereas TLR3 expression was 2-fold higher, along with decrease of TLR2 expression. Expression of TLR 3 was shown to be 3-times higher under the influence of RNA_lig. The effects observed could be potentially applied for suppression of tumor cell chemotaxis by means of these ligands and by influencing different pathways ofchemotaxis regulation.